(untitled) (Ustozlar uchun, 2024)
Annotation: (Arabic – black tree) – tall tree. Musical instrument. It is widely used in Arab, Turkish, Persian, Caucasian (Azerbaijani, Armenian) and Central Asian (Uzbek, Tajik) peoples. A large, pear-shaped calyx with a thin lid and a short, wide handle. This article provides a lot of information about the oud